DIETARY FIBERS IN PROBIOTICS AND HUMAN HEALTH - IRENE PRINCESS JOHN,; G.KALAICHELVAN, (International Journal of Pharma and Bio Sciences, 2016)
Dietary fiber is a class of compounds, mainly of carbohydrate polysaccharides and other polymers including lignin, which, when ingested in the form of plant material, escapes hydrolysis, digestion and absorption in the small intestine, with complete or partial fermentation in the human large intestine. Dietary fibers also include oligosaccharides and lignin and associated plant substances like wax compounds, suberin and cutin. Dietary fibers bring about a range of physiological effects in humans, which in turn confer various health benefits. In developed countries, several gastrointestinal disorders (duodenal ulcers, appendicitis, haemorrhoids, colon carcinomas, constipation), diabetes, cardiovascular diseases, obesity have very low incidence among people consuming high amounts of fiber rich food. Also, previous studies in humans have suggested that dietary fibers lead to a reduction in potentially harmful microbial metabolites.